Appearance
❓Given an algorithm: First step, set m=a; second step, if b<m, then set m=b and output m; otherwise, proceed to the third step; third step, if c<m, then set m=c and output m; otherwise, output "no solution". If a=3, b=6, c=2, then the result of executing this algorithm is ( )A: 3B: 6C: 2D: No solution
💡First, we set ( m = a ). Given ( a = 3 ), we have ( m = 3 ).Next, we compare ( b ) with ( m ). Since ( b = 6 ) and ( 6 ) is not less than ( 3 ), we do not update ( m ) and move to the next step.Finally, we compare ( c ) with ( m ). Since ( c = 2 ) and ( 2 ) is less than ( 3 ), we update ( m ) to ( 2 ) and output ( m ).Therefore, the result of executing the algorithm is ( 2 ).
❓How many distinct sequences of five letters can be made from the letters in QUALITY if each sequence must begin with L, end with Q, and no letter can appear in a sequence more than once?
💡First, identify the letters in "QUALITY": Q, U, A, L, I, T, Y (7 unique letters).The sequence must start with L and end with Q, so the structure is L _ _ _ Q.This leaves 5 letters (U, A, I, T, Y) to fill the three middle positions.For the second position, there are 5 choices.After choosing the second letter, 4 letters remain for the third position.After choosing the third letter, 3 letters remain for the fourth position.Multiply the number of choices for each position: 5 × 4 × 3 = 60.Therefore, there are 60 distinct sequences.
❓A rectangular band formation is a setup with m band members in each of r rows, where m and r are integers. A particular band has fewer than 100 band members. The director arranges them in a rectangular formation and finds that he has three members left over. If he increases the number of members in each row by 1 and reduces the number of rows by 3, there are exactly enough places in the new formation for each band member. What is the largest number of members the band could have?
💡Let's denote the number of band members as ( N ). According to the problem, when the band is arranged in a rectangular formation with ( m ) members in each of ( r ) rows, there are three members left over. This gives us the equation:[N = m times r + 3]When the number of members in each row is increased by 1 and the number of rows is reduced by 3, the formation exactly fits all the members. This gives us the second equation:[N = (m + 1) times (r - 3)]We now have two equations:1. ( N = m times r + 3 )2. ( N = (m + 1) times (r - 3) )Setting these equal to each other:[m times r + 3 = (m + 1) times (r - 3)]Expanding the right-hand side:[m times r + 3 = m times r - 3m + r - 3]Subtracting ( m times r ) from both sides:[3 = -3m + r - 3]Rearranging terms:[6 = r - 3m]This simplifies to:[r = 3m + 6]We also know that ( N < 100 ). Substituting ( r = 3m + 6 ) into the first equation:[N = m times (3m + 6) + 3 = 3m^2 + 6m + 3]We need ( N < 100 ):[3m^2 + 6m + 3 < 100]Subtracting 100 from both sides:[3m^2 + 6m - 97 < 0]Dividing by 3:[m^2 + 2m - frac{97}{3} < 0]Approximating ( frac{97}{3} ) as 32.333, we solve the quadratic inequality:[m^2 + 2m - 32.333 < 0]Using the quadratic formula to find the roots:[m = frac{-2 pm sqrt{4 + 129.332}}{2} = frac{-2 pm sqrt{133.332}}{2}]Approximating ( sqrt{133.332} approx 11.55 ):[m = frac{-2 + 11.55}{2} approx 4.775]Since ( m ) must be an integer, the possible values are ( m = 4 ) and ( m = 5 ).For ( m = 4 ):[r = 3(4) + 6 = 18][N = 4 times 18 + 3 = 75]For ( m = 5 ):[r = 3(5) + 6 = 21][N = 5 times 21 + 3 = 108]Since ( N < 100 ), the largest possible value is ( N = 75 ).
❓Alex makes luxury dresses out of silk. Each dress needs 5 meters of silk and Alex has 600 meters of silk in storage. He gives some of his friends a certain amount of silk each to learn how to make these dresses. He uses the rest to make dresses himself and can make 100 dresses. How many friends did Alex give silk to?
💡First, I need to determine how much silk Alex used to make the 100 dresses himself. Since each dress requires 5 meters of silk, the total silk used for the dresses is 100 dresses multiplied by 5 meters per dress, which equals 500 meters.Next, I'll calculate the amount of silk Alex gave to his friends by subtracting the silk used for the dresses from the total silk he had. This is 600 meters minus 500 meters, resulting in 100 meters of silk given to friends.Assuming each friend received the same amount of silk needed to make one dress, which is 5 meters, I can find the number of friends by dividing the total silk given to friends by the silk per dress. This is 100 meters divided by 5 meters per friend, which equals 20 friends.Therefore, Alex gave silk to 20 friends.
❓Given that 3sin alpha - 2cos alpha = 0, find the value of the following expressions:(1) frac{cos alpha - sin alpha}{cos alpha + sin alpha} + frac{cos alpha + sin alpha}{cos alpha - sin alpha};(2) sin^2alpha - 2sin alphacos alpha + 4cos^2alpha.
💡Alright, so I have this problem here where I'm given that (3sin alpha - 2cos alpha = 0), and I need to find the values of two expressions. Let me try to figure this out step by step.First, the equation (3sin alpha - 2cos alpha = 0) seems like it can be manipulated to find a relationship between (sin alpha) and (cos alpha). Maybe I can solve for one in terms of the other. Let me try that.Starting with (3sin alpha - 2cos alpha = 0), I can rearrange this to get (3sin alpha = 2cos alpha). If I divide both sides by (cos alpha), assuming (cos alpha neq 0), I get (3tan alpha = 2). So, (tan alpha = frac{2}{3}). Okay, that's useful because tangent relates sine and cosine.Now, moving on to the first expression: (frac{cos alpha - sin alpha}{cos alpha + sin alpha} + frac{cos alpha + sin alpha}{cos alpha - sin alpha}). Hmm, this looks a bit complicated, but maybe I can simplify it by using the value of (tan alpha) I found earlier.Let me denote (t = tan alpha = frac{2}{3}). Then, I can rewrite the expression in terms of (t). Since (tan alpha = frac{sin alpha}{cos alpha}), I can express (sin alpha) as (t cos alpha). Let me substitute that into the expression.So, the first fraction becomes (frac{cos alpha - t cos alpha}{cos alpha + t cos alpha}). I can factor out (cos alpha) from numerator and denominator: (frac{cos alpha(1 - t)}{cos alpha(1 + t)}). The (cos alpha) terms cancel out, leaving (frac{1 - t}{1 + t}).Similarly, the second fraction is (frac{cos alpha + t cos alpha}{cos alpha - t cos alpha}). Again, factoring out (cos alpha), we get (frac{cos alpha(1 + t)}{cos alpha(1 - t)}), which simplifies to (frac{1 + t}{1 - t}).So, the entire expression becomes (frac{1 - t}{1 + t} + frac{1 + t}{1 - t}). Now, I can substitute (t = frac{2}{3}) into this.Calculating the first term: (frac{1 - frac{2}{3}}{1 + frac{2}{3}} = frac{frac{1}{3}}{frac{5}{3}} = frac{1}{5}).Calculating the second term: (frac{1 + frac{2}{3}}{1 - frac{2}{3}} = frac{frac{5}{3}}{frac{1}{3}} = 5).Adding these together: (frac{1}{5} + 5 = frac{1}{5} + frac{25}{5} = frac{26}{5}). Wait, that doesn't seem right because the initial calculation in the problem statement got 6. Did I make a mistake?Let me double-check. Maybe I messed up the substitution or the simplification. Let's go back.Original expression: (frac{cos alpha - sin alpha}{cos alpha + sin alpha} + frac{cos alpha + sin alpha}{cos alpha - sin alpha}).I set (t = tan alpha = frac{2}{3}), so (sin alpha = t cos alpha).First fraction: (frac{cos alpha - t cos alpha}{cos alpha + t cos alpha} = frac{1 - t}{1 + t}).Second fraction: (frac{cos alpha + t cos alpha}{cos alpha - t cos alpha} = frac{1 + t}{1 - t}).So, expression becomes (frac{1 - t}{1 + t} + frac{1 + t}{1 - t}).Let me compute this as a single fraction. The common denominator is ((1 + t)(1 - t)).So, (frac{(1 - t)^2 + (1 + t)^2}{(1 + t)(1 - t)}).Expanding numerator: ((1 - 2t + t^2) + (1 + 2t + t^2) = 2 + 2t^2).Denominator: (1 - t^2).So, the expression simplifies to (frac{2 + 2t^2}{1 - t^2}).Factor out 2 in numerator: (frac{2(1 + t^2)}{1 - t^2}).Now, substitute (t = frac{2}{3}):Numerator: (2(1 + (frac{2}{3})^2) = 2(1 + frac{4}{9}) = 2(frac{13}{9}) = frac{26}{9}).Denominator: (1 - (frac{2}{3})^2 = 1 - frac{4}{9} = frac{5}{9}).So, the expression becomes (frac{frac{26}{9}}{frac{5}{9}} = frac{26}{5}). Hmm, that's 5.2, which is 26/5, but the initial problem statement had an answer of 6. I must have done something wrong here.Wait, maybe I misapplied the substitution. Let me try another approach without substituting (t) immediately.Let me consider the original expression:(frac{cos alpha - sin alpha}{cos alpha + sin alpha} + frac{cos alpha + sin alpha}{cos alpha - sin alpha}).Let me denote (A = cos alpha - sin alpha) and (B = cos alpha + sin alpha). Then, the expression is (frac{A}{B} + frac{B}{A}).Which is (frac{A^2 + B^2}{AB}).Compute (A^2 = (cos alpha - sin alpha)^2 = cos^2 alpha - 2sin alpha cos alpha + sin^2 alpha = 1 - 2sin alpha cos alpha).Compute (B^2 = (cos alpha + sin alpha)^2 = cos^2 alpha + 2sin alpha cos alpha + sin^2 alpha = 1 + 2sin alpha cos alpha).So, (A^2 + B^2 = (1 - 2sin alpha cos alpha) + (1 + 2sin alpha cos alpha) = 2).Compute (AB = (cos alpha - sin alpha)(cos alpha + sin alpha) = cos^2 alpha - sin^2 alpha = cos 2alpha).So, the expression becomes (frac{2}{cos 2alpha}).Now, I need to find (cos 2alpha). Since I know (tan alpha = frac{2}{3}), I can use the identity (cos 2alpha = frac{1 - tan^2 alpha}{1 + tan^2 alpha}).Compute (tan^2 alpha = (frac{2}{3})^2 = frac{4}{9}).So, (cos 2alpha = frac{1 - frac{4}{9}}{1 + frac{4}{9}} = frac{frac{5}{9}}{frac{13}{9}} = frac{5}{13}).Therefore, the expression is (frac{2}{frac{5}{13}} = 2 times frac{13}{5} = frac{26}{5}). Wait, that's the same result as before, 26/5, which is 5.2, but the initial problem statement had an answer of 6. I must be missing something.Wait, maybe I made a mistake in the initial substitution. Let me check the problem again.The problem says (3sin alpha - 2cos alpha = 0), so (3sin alpha = 2cos alpha), which gives (tan alpha = frac{2}{3}). That seems correct.Then, for the first expression, I tried two methods: one by substituting (t = frac{2}{3}) and another by expressing in terms of (cos 2alpha). Both gave me (frac{26}{5}), which is 5.2, but the initial answer was 6. Maybe I need to check my algebra again.Wait, in the first method, when I substituted (t = frac{2}{3}) into (frac{1 - t}{1 + t} + frac{1 + t}{1 - t}), I got (frac{1}{5} + 5 = frac{26}{5}). But let me compute (frac{1 - frac{2}{3}}{1 + frac{2}{3}} + frac{1 + frac{2}{3}}{1 - frac{2}{3}}):First term: (frac{frac{1}{3}}{frac{5}{3}} = frac{1}{5}).Second term: (frac{frac{5}{3}}{frac{1}{3}} = 5).Adding them: (frac{1}{5} + 5 = frac{1 + 25}{5} = frac{26}{5}). So that's correct.But the initial problem statement had an answer of 6. Maybe the problem was different? Wait, let me check the problem again.Wait, the problem is:(1) (frac{cos alpha - sin alpha}{cos alpha + sin alpha} + frac{cos alpha + sin alpha}{cos alpha - sin alpha}).(2) (sin^2alpha - 2sin alphacos alpha + 4cos^2alpha).So, for part (1), I get 26/5, which is 5.2, but the initial problem statement had an answer of 6. Maybe I made a mistake in the initial substitution.Wait, maybe I should express everything in terms of sine and cosine without using tangent. Let me try that.Given (3sin alpha = 2cos alpha), so (sin alpha = frac{2}{3}cos alpha).Let me compute (cos alpha - sin alpha = cos alpha - frac{2}{3}cos alpha = frac{1}{3}cos alpha).Similarly, (cos alpha + sin alpha = cos alpha + frac{2}{3}cos alpha = frac{5}{3}cos alpha).So, the first fraction is (frac{frac{1}{3}cos alpha}{frac{5}{3}cos alpha} = frac{1}{5}).The second fraction is (frac{frac{5}{3}cos alpha}{frac{1}{3}cos alpha} = 5).Adding them: (frac{1}{5} + 5 = frac{26}{5}). So, same result.Wait, maybe the problem was different? Or perhaps I misread it. Let me check again.Wait, the problem says (3sin alpha - 2cos alpha = 0), so (3sin alpha = 2cos alpha), which is correct.Alternatively, maybe I should find the actual values of (sin alpha) and (cos alpha). Let me try that.Since (tan alpha = frac{2}{3}), I can think of a right triangle where the opposite side is 2 and the adjacent side is 3, so the hypotenuse is (sqrt{2^2 + 3^2} = sqrt{13}).Therefore, (sin alpha = frac{2}{sqrt{13}}) and (cos alpha = frac{3}{sqrt{13}}).Now, let's compute the first expression:(frac{cos alpha - sin alpha}{cos alpha + sin alpha} + frac{cos alpha + sin alpha}{cos alpha - sin alpha}).Substituting the values:First fraction: (frac{frac{3}{sqrt{13}} - frac{2}{sqrt{13}}}{frac{3}{sqrt{13}} + frac{2}{sqrt{13}}} = frac{frac{1}{sqrt{13}}}{frac{5}{sqrt{13}}} = frac{1}{5}).Second fraction: (frac{frac{3}{sqrt{13}} + frac{2}{sqrt{13}}}{frac{3}{sqrt{13}} - frac{2}{sqrt{13}}} = frac{frac{5}{sqrt{13}}}{frac{1}{sqrt{13}}} = 5).Adding them: (frac{1}{5} + 5 = frac{26}{5}). So, same result again.Wait, but the initial problem statement had an answer of 6. Maybe I'm misunderstanding the problem. Let me check the problem statement again.Wait, the user provided the problem, and then the initial answer had part (1) as 6 and part (2) as 28/13. But when I compute, I get 26/5 for part (1). There must be a mistake somewhere.Wait, maybe I made a mistake in the initial substitution. Let me try another approach.Let me consider the expression (frac{cos alpha - sin alpha}{cos alpha + sin alpha} + frac{cos alpha + sin alpha}{cos alpha - sin alpha}).Let me denote (x = cos alpha) and (y = sin alpha). Then, the expression becomes (frac{x - y}{x + y} + frac{x + y}{x - y}).Combine the fractions: (frac{(x - y)^2 + (x + y)^2}{(x + y)(x - y)}).Expanding numerator: (x^2 - 2xy + y^2 + x^2 + 2xy + y^2 = 2x^2 + 2y^2).Denominator: (x^2 - y^2).So, the expression is (frac{2(x^2 + y^2)}{x^2 - y^2}).Since (x^2 + y^2 = 1), this simplifies to (frac{2}{x^2 - y^2}).Now, (x^2 - y^2 = cos^2 alpha - sin^2 alpha = cos 2alpha).So, the expression is (frac{2}{cos 2alpha}).Now, we need to find (cos 2alpha). Given that (tan alpha = frac{2}{3}), we can use the identity (cos 2alpha = frac{1 - tan^2 alpha}{1 + tan^2 alpha}).Compute (tan^2 alpha = (frac{2}{3})^2 = frac{4}{9}).So, (cos 2alpha = frac{1 - frac{4}{9}}{1 + frac{4}{9}} = frac{frac{5}{9}}{frac{13}{9}} = frac{5}{13}).Therefore, the expression becomes (frac{2}{frac{5}{13}} = 2 times frac{13}{5} = frac{26}{5}), which is 5.2.Wait, so all methods lead me to 26/5, but the initial problem statement had an answer of 6. I must be missing something. Maybe the problem was different? Or perhaps I made a mistake in interpreting the problem.Wait, let me check the problem again:Given that (3sin alpha - 2cos alpha = 0), find the value of the following expressions:(1) (frac{cos alpha - sin alpha}{cos alpha + sin alpha} + frac{cos alpha + sin alpha}{cos alpha - sin alpha});(2) (sin^2alpha - 2sin alphacos alpha + 4cos^2alpha).So, part (1) is as I computed, but the initial answer was 6. Maybe the initial answer was incorrect. Alternatively, perhaps I made a mistake in the calculation.Wait, let me compute (frac{26}{5}) which is 5.2, but 6 is 6.0. They are different. Maybe I should check the problem again.Wait, perhaps I misread the problem. Let me check the original problem again.Wait, the user wrote:Given that (3sin alpha - 2cos alpha = 0), find the value of the following expressions:(1) (frac{cos alpha - sin alpha}{cos alpha + sin alpha} + frac{cos alpha + sin alpha}{cos alpha - sin alpha});(2) (sin^2alpha - 2sin alphacos alpha + 4cos^2alpha).So, that's correct. Then, in the initial answer, part (1) was 6, but my calculation gives 26/5. Maybe the initial answer was wrong.Alternatively, maybe I made a mistake in the calculation. Let me try to compute part (2) to see if I get the same result as the initial answer.Part (2): (sin^2alpha - 2sin alphacos alpha + 4cos^2alpha).Let me express this in terms of (tan alpha = frac{2}{3}).First, divide numerator and denominator by (cos^2 alpha):(frac{sin^2alpha - 2sin alphacos alpha + 4cos^2alpha}{sin^2alpha + cos^2alpha}).Since (sin^2alpha + cos^2alpha = 1), the expression simplifies to (sin^2alpha - 2sin alphacos alpha + 4cos^2alpha).Express in terms of (tan alpha):(tan^2alpha - 2tan alpha + 4).Substitute (tan alpha = frac{2}{3}):((frac{2}{3})^2 - 2(frac{2}{3}) + 4 = frac{4}{9} - frac{4}{3} + 4).Convert to ninths:(frac{4}{9} - frac{12}{9} + frac{36}{9} = frac{4 - 12 + 36}{9} = frac{28}{9}).Wait, but the initial answer was (frac{28}{13}). Hmm, that's different. So, I must have made a mistake.Wait, let me compute it again.(sin^2alpha - 2sin alphacos alpha + 4cos^2alpha).Express in terms of (tan alpha):Divide numerator and denominator by (cos^2 alpha):(frac{tan^2alpha - 2tan alpha + 4}{1}).Wait, no, that's not correct. Because the original expression is (sin^2alpha - 2sin alphacos alpha + 4cos^2alpha), which is equal to (tan^2alpha - 2tan alpha + 4) only if we divide by (cos^2 alpha), but since we're not dividing by anything, that approach might not be correct.Wait, actually, let me factor out (cos^2 alpha):(sin^2alpha - 2sin alphacos alpha + 4cos^2alpha = cos^2alpha(tan^2alpha - 2tan alpha + 4)).Since (cos^2alpha = frac{1}{1 + tan^2alpha} = frac{1}{1 + frac{4}{9}} = frac{9}{13}).So, the expression becomes (frac{9}{13}(frac{4}{9} - frac{4}{3} + 4)).Compute inside the parentheses:(frac{4}{9} - frac{12}{9} + frac{36}{9} = frac{28}{9}).Multiply by (frac{9}{13}): (frac{28}{9} times frac{9}{13} = frac{28}{13}).Ah, okay, so that gives (frac{28}{13}), which matches the initial answer. So, part (2) is correct.But for part (1), I keep getting (frac{26}{5}), which is 5.2, but the initial answer was 6. I must have made a mistake somewhere.Wait, maybe I should compute part (1) using the actual values of (sin alpha) and (cos alpha).Given (tan alpha = frac{2}{3}), so (sin alpha = frac{2}{sqrt{13}}) and (cos alpha = frac{3}{sqrt{13}}).Compute (frac{cos alpha - sin alpha}{cos alpha + sin alpha} + frac{cos alpha + sin alpha}{cos alpha - sin alpha}).First fraction: (frac{frac{3}{sqrt{13}} - frac{2}{sqrt{13}}}{frac{3}{sqrt{13}} + frac{2}{sqrt{13}}} = frac{frac{1}{sqrt{13}}}{frac{5}{sqrt{13}}} = frac{1}{5}).Second fraction: (frac{frac{3}{sqrt{13}} + frac{2}{sqrt{13}}}{frac{3}{sqrt{13}} - frac{2}{sqrt{13}}} = frac{frac{5}{sqrt{13}}}{frac{1}{sqrt{13}}} = 5).Adding them: (frac{1}{5} + 5 = frac{26}{5}).So, that's consistent. Therefore, the initial answer of 6 must be incorrect. Maybe the problem was different, or perhaps there was a typo.Alternatively, maybe I misread the problem. Let me check again.Wait, the problem is:(1) (frac{cos alpha - sin alpha}{cos alpha + sin alpha} + frac{cos alpha + sin alpha}{cos alpha - sin alpha}).Yes, that's correct. So, unless there's a different interpretation, I think my answer is correct.Wait, maybe the problem was supposed to be (frac{cos alpha - sin alpha}{cos alpha + sin alpha} times frac{cos alpha + sin alpha}{cos alpha - sin alpha}), but that would be 1, which doesn't make sense. Alternatively, maybe it's a different expression.Alternatively, perhaps the problem was supposed to be (frac{cos alpha - sin alpha}{cos alpha + sin alpha} + frac{cos alpha + sin alpha}{sin alpha - cos alpha}), but that would give a different result.Alternatively, maybe I made a mistake in the initial step. Let me try to compute the expression numerically.Given (tan alpha = frac{2}{3}), so (alpha = arctan(frac{2}{3})). Let me compute (cos alpha) and (sin alpha).Compute (cos alpha = frac{3}{sqrt{13}} approx 0.83205), (sin alpha = frac{2}{sqrt{13}} approx 0.5547).Compute (cos alpha - sin alpha approx 0.83205 - 0.5547 = 0.27735).Compute (cos alpha + sin alpha approx 0.83205 + 0.5547 = 1.38675).First fraction: (frac{0.27735}{1.38675} approx 0.2).Second fraction: (frac{1.38675}{0.27735} approx 5).Adding them: (0.2 + 5 = 5.2), which is 26/5.So, numerically, it's 5.2, which is 26/5, not 6. Therefore, the initial answer must be incorrect.Therefore, I think my answer is correct, and the initial answer had a mistake.So, for part (1), the correct answer is (frac{26}{5}), and for part (2), it's (frac{28}{13}).But since the initial answer had part (1) as 6, maybe I should double-check.Wait, maybe I made a mistake in the initial substitution. Let me try to compute the expression again.Given (tan alpha = frac{2}{3}), so (sin alpha = frac{2}{sqrt{13}}), (cos alpha = frac{3}{sqrt{13}}).Compute (frac{cos alpha - sin alpha}{cos alpha + sin alpha} + frac{cos alpha + sin alpha}{cos alpha - sin alpha}).First fraction: (frac{frac{3}{sqrt{13}} - frac{2}{sqrt{13}}}{frac{3}{sqrt{13}} + frac{2}{sqrt{13}}} = frac{frac{1}{sqrt{13}}}{frac{5}{sqrt{13}}} = frac{1}{5}).Second fraction: (frac{frac{3}{sqrt{13}} + frac{2}{sqrt{13}}}{frac{3}{sqrt{13}} - frac{2}{sqrt{13}}} = frac{frac{5}{sqrt{13}}}{frac{1}{sqrt{13}}} = 5).Adding them: (frac{1}{5} + 5 = frac{26}{5}).Yes, that's correct. So, the initial answer of 6 must be wrong.Therefore, I think the correct answers are:(1) (frac{26}{5})(2) (frac{28}{13})But since the initial answer had (1) as 6, maybe I should check if there's another way to interpret the problem.Wait, maybe the problem was supposed to be (frac{cos alpha - sin alpha}{cos alpha + sin alpha} times frac{cos alpha + sin alpha}{cos alpha - sin alpha}), but that would be 1, which doesn't make sense.Alternatively, maybe the problem was supposed to be (frac{cos alpha - sin alpha}{cos alpha + sin alpha} + frac{cos alpha + sin alpha}{sin alpha - cos alpha}), but that would give a different result.Alternatively, maybe I made a mistake in the initial step. Let me try to compute the expression again.Wait, another approach: Let me express everything in terms of (sin alpha) and (cos alpha), and then use the given equation to find a relationship.Given (3sin alpha = 2cos alpha), so (sin alpha = frac{2}{3}cos alpha).Let me substitute this into the expression:(frac{cos alpha - frac{2}{3}cos alpha}{cos alpha + frac{2}{3}cos alpha} + frac{cos alpha + frac{2}{3}cos alpha}{cos alpha - frac{2}{3}cos alpha}).Simplify numerator and denominator:First fraction: (frac{frac{1}{3}cos alpha}{frac{5}{3}cos alpha} = frac{1}{5}).Second fraction: (frac{frac{5}{3}cos alpha}{frac{1}{3}cos alpha} = 5).Adding them: (frac{1}{5} + 5 = frac{26}{5}).Same result again. Therefore, I think the initial answer of 6 is incorrect.Therefore, I conclude that the correct answer for part (1) is (frac{26}{5}), and for part (2) is (frac{28}{13}).
❓At a hotel one night, 260 rooms were booked. Some were single rooms and some were double rooms. The single rooms cost a certain amount each and the double rooms cost 60 dollars. The hotel made 14000 dollars that night and there were 196 double rooms booked. How much did each single room cost?
💡First, determine the number of single rooms booked by subtracting the number of double rooms from the total rooms booked: 260 - 196 = 64 single rooms.Next, calculate the total revenue generated from the double rooms: 196 rooms × 60 = 11,760.Subtract the revenue from double rooms from the total revenue to find the revenue from single rooms: 14,000 - 11,760 = 2,240.Finally, divide the revenue from single rooms by the number of single rooms to find the cost per single room: 2,240 ÷ 64 = 35.